No Association between Neck Circumference and Free Triiodothyronine in Euthyroid Men - Jian, Chaohui (Int J Endocrinol, 2021)
OBJECTIVE: Neck circumference (NC) is a simple anthropometric index for the assessment of upper body obesity. Thyroid hormones are closely related to obesity, body fat distribution indicators, and metabolic parameters. However, there are currently no reports on the association between NC and thyroid hormones in the Chinese population. This study aimed to explore the relationship between NC and thyroid hormones in men with normal thyroid function. METHODS: A total of 737 euthyroid men from Shanghai communities were enrolled. Anthropometric parameters, including NC and waist circumference (WC), were measured. Serum thyroid hormones were measured by electrochemical luminescence immunoassay. RESULTS: NC, WC, and body mass index (BMI) were significantly positively correlated with serum free triiodothyronine (FT3) (all P < 0.05). FT3 levels all presented significant upward trends with the increase in NC, WC, or BMI quartiles (all P for trend < 0.05), whereas there were no significant correlations between the three obesity indices and free thyroxine or thyroid-stimulating hormone (both P > 0.05). After adjustment for metabolic confounding factors such as age, blood pressure, blood glucose, lipid profiles, and CRP in multiple linear regression analysis, the correlation between FT3 and NC disappeared (standardized β = −0.015, P=0.705), and FT3 remained significantly associated with WC (standardized β = 0.103, P=0.012) and BMI (standardized β = 0.082, P=0.047). CONCLUSIONS: In euthyroid men from Shanghai communities, there was no independent correlation between serum FT3 levels and NC. The trial was registered with ChiCTR1900024011.